2023
DOI: 10.1021/acsabm.3c00162
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Facilitated Crystallization of Spray-Dried CD-MOFs with Tunable Morphology, Porosity, And Dissolution Profile

Abstract: Metal–organic frameworks (MOFs) with versatile functionalities have applications in environmental science, sensor separation, catalysis, and drug delivery. In particular, MOFs used in drug delivery should be biodegradable and easy to control. In this study, spray-dried cyclodextrin-based MOFs (CD-MOFs) with tunable crystallinity, porosity, and dissolution properties were fabricated. The spray-drying precursor properties, such as ethanol volume ratio, incubation time, and precursor concentration, were optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The articles catalogued in Table 3 primarily center on MOF-based transdermal systems as a potential remedy for melanoma and an array of wounds such as diabetic, chronic, and infected wounds. CD-MOFs have shown to be able to encapsulate various drugs and active compounds, including doxorubicin, 176,177 resveratrol, 140,178 epigallocatechin gallate, 179 vitamin A palmitate, 180 ascorbic acid derivatives, 181 myricetin, 182 ketoconazole, 183 salicylic acid, 140 ferulic acid, 140,163 different NSAIDs, 184 emodin and quercetin. 128…”
Section: Efficacy Of Cd-mof Transdermal Drug Delivery Systemsmentioning
confidence: 99%
“…The articles catalogued in Table 3 primarily center on MOF-based transdermal systems as a potential remedy for melanoma and an array of wounds such as diabetic, chronic, and infected wounds. CD-MOFs have shown to be able to encapsulate various drugs and active compounds, including doxorubicin, 176,177 resveratrol, 140,178 epigallocatechin gallate, 179 vitamin A palmitate, 180 ascorbic acid derivatives, 181 myricetin, 182 ketoconazole, 183 salicylic acid, 140 ferulic acid, 140,163 different NSAIDs, 184 emodin and quercetin. 128…”
Section: Efficacy Of Cd-mof Transdermal Drug Delivery Systemsmentioning
confidence: 99%
“…Manipulating these parameters during their synthesis can result in MOFs with completely different characteristics. This has led many researchers to study MOFs due to their wide range of potential applications, such as catalysts, 11 electrochemical and chemical sensors, 12 encapsulating large molecules, 13 enzymes, 14,15 storing gas, 16,17 removal of hazardous heavy metals, 18 organic dyes and toxins, [19][20][21] water splitting, 22 exhibiting anti-bacterial and anti-cancer activities, [23][24][25][26] facilitating drug delivery [27][28][29][30] and etc. MOFs can be used as a source for releasing metal ions under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of MOFs depends on the raw material costs (ligands, metal sources and solvents) and the manufacturing process (product recovery by filtration and other means, washing, drying, forming and processing), including capital investment, process energy, utilities and labor costs. 9,10 To address process simplification and cost reduction, various synthesis methods have been demonstrated, including solvothermal, hydrothermal, microwave-assisted, 11,12 sonochemical, 13,14 microfluidic, 15,16 aqueous solution, 17,18 spray-drying 19–22 and mechanochemical methods. 23–27 To date, the most conventional and common method for obtaining CD-MOF crystals is the vapor diffusion method.…”
mentioning
confidence: 99%
“…It has already been reported that even if the structure of CD-MOF is amorphous, it has potential applications as a drug carrier. 21,22 The lack of potassium (especially under conditions of K + /CD < 1) causes defects in the CD bonds, resulting in reduced crystallinity, as shown in Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation